2015
DOI: 10.1017/s000711451500313x
|View full text |Cite|
|
Sign up to set email alerts
|

A randomised trial of a medium-chain TAG diet as treatment for dogs with idiopathic epilepsy

Abstract: Despite appropriate antiepileptic drug treatment, approximately one-third of humans and dogs with epilepsy continue experiencing seizures, emphasising the importance for new treatment strategies to improve the quality of life of people or dogs with epilepsy. A 6-month prospective, randomised, double-blinded, placebo-controlled cross-over dietary trial was designed to compare a ketogenic medium-chain TAG diet (MCTD) with a standardised placebo diet in chronically antiepileptic drug-treated dogs with idiopathic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(105 citation statements)
references
References 53 publications
6
99
0
Order By: Relevance
“…It was not a "ketogenic" diet, and thus may be less effective for some dogs than it was for Case 2. [13][14][15] The need for alternatives to current AEDs in dogs is underscored by their lack of efficacy in some cases and harmful side effects in others, 4 including-as detailed in Case 1's report-liver damage from prolonged use of phenobarbital. Anecdotally, Case 1's owners also reported that while in the process of researching his condition and customizing his diet, ingestion of a nonketogenic treat seemed to trigger a seizure event.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was not a "ketogenic" diet, and thus may be less effective for some dogs than it was for Case 2. [13][14][15] The need for alternatives to current AEDs in dogs is underscored by their lack of efficacy in some cases and harmful side effects in others, 4 including-as detailed in Case 1's report-liver damage from prolonged use of phenobarbital. Anecdotally, Case 1's owners also reported that while in the process of researching his condition and customizing his diet, ingestion of a nonketogenic treat seemed to trigger a seizure event.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, relatively few modern dogs subsist primarily on raw meat or even any raw meat, and no scientific data has yet to confirm its benefits in controlling epilepsy in canines. 13 This KMCT diet also reduced a subset of attention-deficit/hyperactivity disorder-like features noted in the dogs with epilepsy, including chasing and strangerdirected fear. 2 Clearly, laboratory-based rats and mice have significant advantages (ie, limited variability, environmental control, opportunities for genetic modification, rapid growth and reproduction, and relatively low cost).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The study failed to identify a difference in seizure frequency between the groups and 3 of 9 dogs fed the ketogenic diet developed pancreatitis. In contrast, a medium chain triglyceride (MCT)‐based diet developed for the treatment of cognitive dysfunction in dogs111 was evaluated in dogs with idiopathic epilepsyin, a 6‐month prospective, randomized, double‐blinded, placebo‐controlled crossover dietary trial 112. Seizure frequency and monthly seizure days were significantly lower in the 21 dogs finishing the trial when on the test diet for 12 weeks as compared to those on the placebo diet.…”
Section: What Alternative Nonpharmacologic Treatments Are Available?mentioning
confidence: 99%